1977
DOI: 10.1073/pnas.74.8.3287
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of human interferon by Xenopus laevis oocytes: two structural genes for interferons in human cells.

Abstract: Human fibroblasts and leukocytes produce interferons which may be distinguished by their antigenic and species specificity as well as by their molecular weight distributions. To elucidate the basis or these differences, we isolated mRNA from induced human fibroblasts and lymphoblastoid (Namalva) cells and studied the products of translation in Xenopus Iaevis oocytes. The mRNA from the respective cells yielded translation products, in oocytes, that were characteristic of the cells from which the mRNA was derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…We concluded that two separate structural genes are likely to exist for these two antigenic species of human interferon (Cavalieri et al 1977). These earlier results and the present data suggest that both interferon genes are expressed during the induction of Namalva cells.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We concluded that two separate structural genes are likely to exist for these two antigenic species of human interferon (Cavalieri et al 1977). These earlier results and the present data suggest that both interferon genes are expressed during the induction of Namalva cells.…”
Section: Discussionsupporting
confidence: 71%
“…Preliminary investigations carried out in this laboratory revealed that Namalva interferon is not completely neutralized by either specific antileukocyte or anti-fibroblast interferon sera; however, a mixture of the anti-leukocyte and anti-fibroblast interferon sera did cause complete neutralization of the antiviral activity of Namalva interferon (Cavalieri et al 1977).…”
Section: Fractionation Of Namalva Interferon By Means Of Antibody Affmentioning
confidence: 99%
“…They differ biologically, chemically, and physically. In addition, it has been shown that leukocyte and fibroblast interferons are products of different structural genes (6). Although a great deal of research has been directed toward an understanding of the molecular mechanism of interferon induction and activity, progress has been slow due largely to the small amounts of pure interferon protein and mRNA for study.…”
mentioning
confidence: 99%
“…Although there are many lymphoblast cell lines that grow readily in culture (8,13), only the Burkitt's lymphoma-derived Namalva cell line has been shown to produce amounts of interferon substantial enough to warrant its use in large-scale production (9,18). Namalva cells yield both human leukocyte and human fibroblast interferon (2,5). In this report, we summarize the results of screening human B-lymphoblast and other leukocyte-derived cell lines for interferon production.…”
mentioning
confidence: 99%